Identification of a Novel RAMA/RON3 Rhoptry Protein Complex in Plasmodium falciparum Merozoites - Ito, Daisuke; Chen, Jun-Hu; Takashima, Eizo; Hasegawa, Tomoyuki; Otsuki, Hitoshi; Takeo, Satoru; Thongkukiatkul, Amporn; Han, Eun-Taek; Tsuboi, Takafumi (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria causes a half a million deaths annually. The parasite intraerythrocytic lifecycle in the human bloodstream is the major cause of morbidity and mortality. Apical organelles of merozoite stage parasites are involved in the invasion of erythrocytes. A limited number of apical organellar proteins have been identified and characterized for their roles during erythrocyte invasion or subsequent intraerythrocytic parasite development. To expand the repertoire of identified apical organellar proteins we generated a panel of monoclonal antibodies against Plasmodium falciparum schizont-rich parasites and screened the antibodies using immunofluorescence assays. Out of 164 hybridoma lines, 12 clones produced monoclonal antibodies yielding punctate immunofluorescence staining patterns in individual merozoites in late schizonts, suggesting recognition of merozoite apical organelles. Five of the monoclonal antibodies were used to immuno-affinity purify their target antigens and these antigens were identified by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Two known apical organelle protein complexes were identified, the high-molecular mass rhoptry protein complex (PfRhopH1/Clags, PfRhopH2, and PfRhopH3) and the low-molecular mass rhoptry protein complex (rhoptry-associated proteins complex, PfRAP1, and PfRAP2). A novel complex was additionally identified by immunoprecipitation, composed of rhoptry-associated membrane antigen (PfRAMA) and rhoptry neck protein 3 (PfRON3) of P. falciparum. We further identified a region spanning amino acids Q221-E481 within the PfRAMA that may associate with PfRON3 in immature schizonts. Further investigation will be required as to whether PfRAMA and PfRON3 interact directly or indirectly.